Core topics in physiology - Rosnah Ismail; Ruby Husain; Saadiah Mohd. Hidir (University of Malaya Press, 2014)
This book focuses on the core topics which include physiology of cell, blood, nerve and synapse, skeletal muscle with neuromuscular junction, reflex, smooth muscle and autonomic nervous system. The notes are concise and easy to understand. The content is based on the syllabus of the Physiology course offered at Faculty of Medicine, University of Malaya. The syllabus will be similar for other medical schools in Malaysia, be it public or private and thus, the book will be very relevant for all students in the health sciences. The authors are experienced physiologist with each of them having more than 25 years of teaching experience. The practice questions provided within the book are what students may see in written or oral examinations (viva-voce) and would help prepare students for a physiology examination.